Practical process control for engineers and technicians - Altmann, Wolfgang; Macdonald, Dave, 1942- (Oxford ; Burlington, MA : Newnes, 2005)
This book is aimed at engineers and technicians who need to have a clear, practical understanding of the essentials of process control, loop tuning and how to optimize the operation of their particular plant or process. The reader would typically be involved in the design, implementation and upgrading of industrial control systems. Mathematical theory has been kept to a minimum with the emphasis throughout on practical applications and useful information. This book will enable the reader to: * Specify and design the loop requirements for a plant using PID control * Identify and apply the essential building blocks in automatic control * Apply the procedures for open and closed loop tuning * Tune control loops with significant dead-times * Demonstrate a clear understanding of analog process control and how to tune analog loops * Explain concepts used by major manufacturers who use the most up-to-date technology in the process control field A practical focus on the optimization of process and plant Readers develop professional competencies, not just theoretical knowledge Reduce dead-time with loop tuning techniques.
Process measurement and transducers -- Basic principles of control valves and actuators -- Fundamentals of control systems -- Stability and control modes of closed loops -- Digital control principles -- Real and ideal PID controllers -- Tuning of PID controllers in both open and closed loop control systems -- Controller output modes, operating equations and cascade control -- Concepts and applications of feedforward control -- Combined feedback and feedforward control -- Long process deadtime in closed loop control and the Smith Predictor -- Basic principles of fuzzy logic and neural networks -- Self-tuning intelligent control and statistical process control.
Includes index.
Keywords: Process control; Production engineering; Electronic books